Permissive Parenting Style and Maladaptive Behavioral Tendencies Among Junior High School Students of Notre Dame of Tacurong College, Mindanao, Philippines - Danika Cabanatuan; Crizjale Ahmad (Universitas Pendidikan Indonesia (UPI), 2022)
Parenting style is an essential factor in the development of children's behavior. But, it should research oppositely. This study determined the relationship between Permissive Parenting Styles and Maladaptive Behavioral tendencies. This study answer: (1) To what extent is the respondents' permissive parenting style experienced? (2) To what degree do respondents manifest maladaptive behavioral tendencies? and (3) is there a significant correlation between permissive parenting style and maladaptive behavioral tendencies of the respondents? The study revealed that parents were most likely to have an amiable attitude towards their children. The parents allow them to express their feelings, form their perspectives, and create their own decisions. They somehow showed considerations about their child's well-being and did not tolerate some stuff such as absences and laziness. Despite having a permissive parent, children have cheated on school tests, lied about their age to gain entrance, purchase liquor, take a cigarette, or even steal money from their parents or other family members. Using a permissive parenting style does not have a significant relationship with their kids in developing maladaptive behavioral tendencies. It is recommended to look for other factors contributing to maladaptive behavior since permissive parenting does not affect maladaptive behavior and try to venture into other parenting styles.